2020
DOI: 10.3390/polym12030519
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Adaptive Metastructures with Variable Bandgap Regions by 4D Printing

Abstract: This article shows how four-dimensional (4D) printing technology can engineer adaptive metastructures that exploit resonating self-bending elements to filter vibrational and acoustic noises and change filtering ranges. Fused deposition modeling (FDM) is implemented to fabricate temperature-responsive shape-memory polymer (SMP) elements with self-bending features. Experiments are conducted to reveal how the speed of the 4D printer head can affect functionally graded prestrain regime, shape recovery and self-ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 33 publications
1
57
0
Order By: Relevance
“…Noorozi et al proposed a finite element based method to simulate the shape recovery and self-bending of 4D printed temperature-responsive SMP. [92] They also discussed the roles of inelastic strain, thermal strain, thermal expansion, elasticity tensor, and stress. All of which were used to depict the stressstrain relationship for the theoretical modeling of SMP followed by presenting the wave propagation model.…”
Section: Mathematical Modeling Of the 4d Printed Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Noorozi et al proposed a finite element based method to simulate the shape recovery and self-bending of 4D printed temperature-responsive SMP. [92] They also discussed the roles of inelastic strain, thermal strain, thermal expansion, elasticity tensor, and stress. All of which were used to depict the stressstrain relationship for the theoretical modeling of SMP followed by presenting the wave propagation model.…”
Section: Mathematical Modeling Of the 4d Printed Samplesmentioning
confidence: 99%
“…[ 7 ] Jessica Rosenkrantz demonstrated nature inspired 3D printed petal shaped panels that can be interconnected by hinges into a single piece garment named the “Kinematics dress.” [ 8 ] The garment behaves like a moveable fabric and reduces printing volume by 85% but costs a lot of money and time for the single piece dress. After this demonstration and advancement of 4D technology, researchers redefined the definition that 3D printed objects exhibited predefined and targeted shapes, in contrast to trivial uniform swelling, under external stimuli such as temperature, [ 9 ] moisture, [ 46 ] light, [ 43 ] electrical or magnetic fields, [ 49,50 ] etc. 4D printed objects’ transformation attributes include bending, twisting, corrugating, and elongating that allowed fabrication of robots, lifters, lockers, toys, microtubes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Noroozi et al [ 61 ] used the 4D printing technology to design adaptive meta-structures which aim to control the propagation of elastic waves. Based on the SMPs’ thermomechanics, adaptive functionally graded (FG) beams were manufactured by 4D printing in order to mitigate vibration and acoustic attenuation.…”
Section: Shape Memory Effect In Polymersmentioning
confidence: 99%
“…Hybrid composite specimens with the SSS stacked on the top of an SMP layer and larger SSS thicknesses gave rise to larger recovery forces. Noroozi et al [ 27 ] reported on 4D printing used for adaptive metastructures that exploited resonating self-bending elements to filter vibrational and acoustic noises. FDM was implemented to fabricate temperature-responsive SMPs with self-bending features.…”
Section: Introductionmentioning
confidence: 99%